A PSYCHOLOGICAL FACTORS THAT INFLUENCE SMARTPHONE ADICTION OF ISLAMIC SCHOOL STUDENTS - Bambang Suryadi; Usni Dwi Ambarwaty Dwi Ambarwaty; Bahrul Hayat; Neneng Tati Sumiat (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
Smartphone addiction is a phenomenon that is developing very fast due to easy accessibility and unique internet-based applications. This study aims to determine the effect of psychological factors (self-control, loneliness, and sensation seeking) on smartphone addiction amongst Islamic school (madrasah) students. This study used a quantitative approach with a sample of 327 students of Islamic School (Madrasah) taken with a non-probability sampling technique. Measuring instruments used in this study were Smartphone Addiction Scale (SAS), 24 Attitudinal Items, UCLA Loneliness Scale, and Sensation Seeking Scale V. Data analysis techniques used multiple regression analysis techniques. The results of the study indicated a significant influence of self-control, loneliness, and sensation seeking on smartphone addiction. Based on the results of hypothesis testing, there are four significant variables, namely self-control, intimate others, social others, and boredom susceptibility. Other variables such as affiliation, belonging, thrill, adventure, and experience seeking are not significant to smartphone addiction.